Effect of repairing and grinding scratched alpine skis on their friction on snow - Kaserer, L.; van Putten, J.; Rohm, S.; Hasler, M.; Nachbauer, W. (Procedia Engineering, 2016)
Ski base service includes filling of scratches, grinding and waxing. The aim of this study was to investigate the effect of scratched and then repaired ski bases on their kinetic friction on snow. Kinetic friction of three different types of skis (junior, women and racing skis) in four preparation steps (factory-new, standard grinded, scratched, repaired) were measured at two different velocities (4 and 8 ms-1). Testing took place on a linear tribometer with defined conditions at -8?C snow temperature. The normal force was set to typical values for the particular ski type. The coefficient of friction of the scratched skis almost doubled compared to the unscratched ones. This may be caused by asperity interlocking between the snow grains and the scratches. The coefficient of friction of the repaired bases was re-established since only about 1% of the before scratched area was covered with the filling material.